Assessment of Malting Performance of Maize and Sorghum of Similar Total Nitrogen Content in Providing the Hydrolytic Enzymes in the Brewing of Gluten-Free Beers. (10th January 2022) - Amadi, O. C.; Moneke, A. N.; Okolo, B. N.; Nwagu, T. N.
Abstract: Malted sorghum is used extensively as source of hydrolytic enzymes in brewing gluten-free beers. Malted barley is often used in combination with un-malted maize adjunct (flakes, grits, flours) to brew non-gluten-free beers. Sorghum and maize are similar in many ways. The potential of using malted maize in brewing gluten-free beers was studied. Sorghum and maize of similar total nitrogen content were malted under comparable conditions. Sorghum and maize grains followed some similar patterns in developing hydrolytic enzymes, measured as diastatic power (DP), when malted. Development of diastatic enzymes in both cereals increased with germination period. When mashed, the hot water extract (HWE) for malted sorghum was similar to malted maize when both had five days of germination. For malted sorghum, the HWE value was already reached after two days of germination. The total soluble nitrogen (TSN) for malted sorghum was, for the five germination times studied, half of the TSN values or less than those found for malted maize. Total soluble nitrogen, indicative of the proteolysis achieved during the malting of cereals, showed good proteolysis for the malted maize. The results suggest that like malted sorghum, malted maize could play a similar role in brewing gluten-free beers.